The Spectrum of Biochemical Alterations with Molecular and Serological Biomarkers in the Diagnosis of COVID-19: Searching for Novel One to Identify Disease Earlier with Better Prognosis and Drug Discovery - Ray, Suman K.; Mukherjee, Sukhes (Recent Advances in Anti-Infective Drug Discovery, 2021)
Clinical and laboratory predictors of progression to serious and deadly forms are crucial in the fight against COVID-19, which has now become a worldwide pandemic. The clinical laboratory's vital role in today's crises has never been more obvious. These subjective clinical signals can be perceived more confidently during an examination with the help of biomarkers. To best combat present and future pandemics, global unity on test access is required, as well as infection prevention and diagnostic measures that are tightly linked.
Keywords: SARS-CoV-2 antigens